Child and parent perceptions of acceptability and therapeutic value of a socially assistive robot used during pediatric rehabilitation. Issue 2 (16th January 2021) - Butchart, Joanna; Harrison, Reema; Ritchie, Jan; Martí, Felip; McCarthy, Chris; Knight, Sarah; Scheinberg, Adam
Abstract: Purpose: Socially assistive robots are emerging as a method of supporting the rehabilitation of children with physical disabilities. To date there has been no in-depth analysis of parent and child perspectives regarding the use of socially assistive robots for pediatric rehabilitation. The purpose of this study was to capture the experiences of parents and children who participated in a rehabilitation session with a socially assistive rehabilitation robot. Methods: An interpretivist qualitative design was used. Semi-structured interviews of five parent-child pairs were undertaken to examine their experiences during a rehabilitation session with the NAO robot. Interviews were analyzed using inductive thematic analysis. Results: Five themes were identified: 1) affective influence, 2) independence, 3) preference for human interaction, 4) accessibility of therapy and 5) familiarity with technology. Conclusion: Based on parent and child perspectives, the NAO robot is an acceptable complement to rehabilitation therapies. Children and parents perceived the NAO robot to have therapeutic value through its potential to enhance engagement, promote child independence during rehabilitation exercises and its potential support a rehabilitation program when a human therapist is not accessible. Implications for rehabilitation: Socially assistive robots are an acceptable tool to support the delivery of exercise programs in pediatric rehabilitation. Therapists need to consider how to provide a positive affective experience during rehabilitation sessions, the use of socially assistive robots may be one method of doing this. When using socially assistive robots to support rehabilitation the individual needs and preferences of the child and family should be considered. Socially assistive robots may have a role in supporting home exercises programs; future work is needed to determine the feasibility of this.